2019
DOI: 10.3390/nano9121704
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Stimuli Responsive Carbon Nanotube Sponge-PDMS Amphibious Actuator

Abstract: A dual-stimuli responsive soft actuator based on the three-dimensional (3D) porous carbon nanotube (CNT) sponge and its composite with polydimethylsiloxane (PDMS) was developed, which can realize both electrothermal and electrochemical actuation. The bimorph actuator exhibited a bending curvature of 0.32 cm−1·W−1 under electrothermal stimulation on land. The displacement of the electrochemical actuator could reach 4 mm under a 5 V applied voltage in liquid. The dual-responsive actuator has demonstrated the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…A primary pre‐gel solution containing monomers and photo‐initiators could form hydrogels with interpenetrating networks at the UV light‐exposed regions. By further incorporation of functional elements such as liquid metals [ 42 ] or 2D materials, [ 43 ] the patterned hydrogels can perform various stimuli‐responsive shape morphing behaviors predictably and thus serve as SFAs.…”
Section: Fabrication Of the Sfasmentioning
confidence: 99%
“…A primary pre‐gel solution containing monomers and photo‐initiators could form hydrogels with interpenetrating networks at the UV light‐exposed regions. By further incorporation of functional elements such as liquid metals [ 42 ] or 2D materials, [ 43 ] the patterned hydrogels can perform various stimuli‐responsive shape morphing behaviors predictably and thus serve as SFAs.…”
Section: Fabrication Of the Sfasmentioning
confidence: 99%
“…Replicating these compound movements observed in nature is still challenging and often requires multitrigger-responsive soft materials capable of volumetric expansion and contraction . There are numerous polymeric materials that produce large-scale actuation upon exposure to a single stimulant such as humidity, light, temperature, pH, and electric/magnetic field. Further, polymeric materials in many different forms such as fibers, , hydrogels, , sponges, , films, and textiles are known to be efficient soft actuators capable of producing programmable actuation. Among these, polymer films have attracted enormous interest because of their abilities to produce macroscale actuation and shape morphing abilities such as folding, twisting, and rolling. , Moreover, polymer film-based actuators exhibit distinct functional locomotions (tumbling, jumping, and wiggling), , and possess tunable actuation time scales spanning from microseconds to several tens of seconds. , A few polymeric film composites consisting of more than one layer are designed to actuate upon exposure to multiple stimulants such as light, heat, electric field, moisture, and solvent vapors. , Usually, integrating multistimuli-responsiveness by combining more than one polymer film increases the complexity of the soft actuator system and reduces its durability.…”
Section: Introductionmentioning
confidence: 99%
“…1 There are numerous polymeric materials that produce large-scale actuation upon exposure to a single stimulant such as humidity, 2−4 light, 5 temperature, 6 pH, 7 and electric/magnetic field. 8−10 Further, polymeric materials in many different forms such as fibers, 11,12 hydrogels, 13,14 sponges, 15,16 films, 17 and textiles 18 are known to be efficient soft actuators capable of producing programmable actuation. Among these, polymer films have attracted enormous interest because of their abilities to produce macroscale actuation and shape morphing abilities such as folding, twisting, and rolling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…silicone oil as a continuous liquid phase and silicone elastomer as a continuous phase of a solid-like system. Silicone oil is used as a carrier liquid in electrorheological suspensions, while silicone elastomer has been proved as a suitable matrix for the preparation of mechanical actuators [43,44]. Our previous research showed that SI-ATRP is a powerful tool for tailoring the ER performance of ER fluids based on graphene oxide and silicone oil [45].…”
Section: Introductionmentioning
confidence: 99%